The luminescence efficiency of green phosphor Ca7(PO4)2(SiO4)2:Eu2+ for white light-emitting diode - Van Liem Bui; Phan Xuan Le (Institute of Advanced Engineering and Science, 2022)
This study examines the green-emission phosphor composition of Eu2+ doped Ca7(PO4)2(SiO4)2 to serve the goal of efficiency enhancement for the white light emitting diode (LED). The process of preparation and photoluminescent investigation of proposed phosphor composition was monitored under near UV excitation wavelength of the LED die. The sample phase was determined using XRD. To explore Ca7(PO4)2(SiO4)2:Eu2+ capabilities, the diffuse reflectance and photoluminescence spectral figures were employed. The ultraviolet absorption of Ca7(PO4)2(SiO4)2:Eu2+ranged from 240 to 440 nm, with a wide band of green emission peaking at 522 nm. Besides the concentration quenching mechanism, we also focus on essential characteristics for white-light-emitting diode(WLED) production like temperature-dependent lumen output and chromaticity coordinates.